One foot in, one foot out: an Accountability Analysis of the United Kingdom’s and Switzerland’s Regulatory Frameworks in the UNCAC Regime. - Jael Lena Gless (UCL Journal of Law and Jurisprudence, 2024)
This comparative analysis of the UK and Switzerland's regulatory frameworks on asset return showcases how two former safe havens for corrupt funds pioneer a novel grid of accountability in discretionary asset returns. This step of the UK and Switzerland is crucial as it fills the gap left by the UN Convention against Corruption, which introduces asset return obligations without guiding the mechanisms and procedures for the process. The comparison highlights how both states have tailored their regulatory framework to the domestic peculiarities of their legal system, serving as a basis for others to follow suit in this uncharted territory. Besides the commitment to accountability, both regulatory frameworks also showcase the importance both states place on protecting their leeway by enshrining the policy to make case-by-case return decisions. Nevertheless, creating standards and boundaries to inform their case-by-case decision-making, enhancing transparency and consistency in the process, is a step in the right direction.
Keywords: UNCAC; Comparative Law; Asset Recovery